“People of Central Asia” as a scientific source - Lamazhaa, Chimiza K.; Tuimebaev, Zhanseit K.; Shagimgereeva, Bakytgul E. (The New Research of Tuva, 2024)
The article analyzes materials from the “People of Central Asia” section of the newspaper “Center of Asia”, which was published in Kyzyl from 1991 to 2017 in Russian. The authors note the significant value of the materials in this section, which the editorial staff published as separate editions over the years (six volumes in total). This section predominantly featured biographical interviews with individuals representing various ethnicities, professions, and places of residence. Until now, Tuvan studies have paid little attention to these texts.Their rich source value is considered relevant to several scientific disciplines, including historical knowledge. The materials not only depict the history spanning the years of the newspaper's publication and conversations with interviewees but also present the history of Tuva over nearly a century and a half (late 19th to 21st centuries) through the reminiscences of eyewitnesses and the retellings by descendants. The political significance of the materials lies in the presence of biographies and self-narratives concerning the beliefs of regional leaders and public figures. The sociological and cultural significance of the interviews is demonstrated through groups of materials categorized by the professions of the interviewees: through the lens of their stories, one can examine the history of science (Tuvan studies), the cultural history of the republic, and so forth. Philologists interested in studying questions of intercultural and interlingual interaction among ethnic groups through press materials may also find “People of Central Asia” of interest.
Keywords: newspaper source; mass media; Tuva; Tuvans; everyday history; post-Soviet Tuva; history of Tuva; Center of Asia; People of Central Asia